2022
DOI: 10.3390/cells11111841
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adipose Tissue Beiging by HIV Integrase Inhibitors, Dolutegravir and Bictegravir, Is Associated with Adipocyte Hypertrophy, Hypoxia, Elevated Fibrosis, and Insulin Resistance in Simian Adipose Tissue and Human Adipocytes

Abstract: For people living with HIV, treatment with integrase-strand-transfer-inhibitors (INSTIs) can promote adipose tissue (AT) gain. We previously demonstrated that INSTIs can induce hypertrophy and fibrosis in AT of macaques and humans. By promoting energy expenditure, the emergence of beige adipocytes in white AT (beiging) could play an important role by limiting excess lipid storage and associated adipocyte dysfunction. We hypothesized that INSTIs could alter AT via beiging inhibition. Fibrosis and gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…Several latest published data seem to confirm our observation. In a recent report, Gorwood et al [36] showed the ability of DTG and RAL to exert pro-adipogenic effects in human/simian adipose tissue and human adipocytes, and Ngono et al confirmed this result in an animal model of SIV-infected macaques, where DTG was associated with higher adipogenesis [39]. In addition, we found that TAF treatment had an inhibitory effect on adipocytic differentiation, acting in the earlier phases through PPARγ expression deregulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Several latest published data seem to confirm our observation. In a recent report, Gorwood et al [36] showed the ability of DTG and RAL to exert pro-adipogenic effects in human/simian adipose tissue and human adipocytes, and Ngono et al confirmed this result in an animal model of SIV-infected macaques, where DTG was associated with higher adipogenesis [39]. In addition, we found that TAF treatment had an inhibitory effect on adipocytic differentiation, acting in the earlier phases through PPARγ expression deregulation.…”
Section: Discussionsupporting
confidence: 78%
“…It has been described the increase of extracellular matrix in adipose tissue by deposition of collagen produced by adipocytes [35, 37] and the reprogramming of adipocytes into fibroblast, confirmed by the expression of ER-TR7, a well-known fibroblastic marker was also reported [38]. In addition, more recently, Ngono et al described the ability of BIC and DTG to induce a pro-fibrotic phenotype in simian beige adipose tissue and found this phenotype to be associated with insulin resistance [39].…”
Section: Introductionmentioning
confidence: 89%
“…TNFA mRNA was not detected in the AT of SIV− group but was present in the SIV+ART+ group; these results suggest that immune-mediated inflammation is present but at a low level in the AT in this setting. We also observed a higher expression of leptin, that was associated with an even higher expression of adiponectin during chronic treated infection; these two hormones exert both metabolic and immunoregulatory functions, their increase can therefore either directly reflect fat gain and lipid storage on ART [45] (in accordance with the increased PPARG mRNA expression) or the onset of an unexpected anti-inflammatory activity [46] Along with the pro-inflammatory cytokine signature and the anti-inflammatory hormone signature we observed only weak signs of AT infiltration by CD45+ (hematopoietic) cells. However, a non-significant increase in IFNG mRNA expression (a T and NK cell marker) suggested that T and NK cells were recruited and/or activated to some extent.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, we found that the PPARG/COL1A2 ratio (a marker of the AT's metabolic status) was abnormally low in the SIV+ART+ group; this might correspond to dysfunctional AT growth, with an imbalance between adipocyte hyperplasia/hypertrophy and expansion of the surrounding collagen fibers. Researchers have observed changes in the AT's cellular architecture in PLWH, with heterogeneous adipocyte size and an increase in fibrosis [45,49]. Moreover, the dysfunction was more prominent in the SCAT than in the VAT, suggesting that the former is more susceptible to the effects of an ART-treated SIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several latest published data seem to confirm our observation. In a recent report, Gorwood et al [36] showed the ability of DTG and RAL to exert pro-adipogenic effects in human/simian adipose tissue and human adipocytes, and Ngono Ayissi et al [39] confirmed this result in an animal model of SIV-infected macaques, where DTG was associated with higher adipogenesis. In addition, we found that TAF treatment had an inhibitory effect on adipocytic differentiation, acting in the earlier phases through PPARγ expression deregulation.…”
Section: Discussionmentioning
confidence: 91%